Synthesis and Characterization of Hydrogel of Chitosan-Poly (N-Vinyl-2-Pirrolidone) (PVP)- Alginate for Ibuprofen Release - Kartini Afriani; Tri Sutanti Budikania (Chemistry Department, The University of Brawijaya, 2020)
Hydrogels chitosan-poly-(N-vinyl-pyrrolidone)-alginate (Ch/PVP/Alg) have been synthesized with Ca2+, Zn2+ and formaldehyde as crosslinker. Hydrogels with ratio polymer 70:20:10 give a high swelling ratio and good network. The Ch/PVP/Alg/Ca2+ has 463.73% swelling ratio and 80.59% gel. Ch/PVP/Alg/Zn has 489.21% swelling ratio and 81.67% gel. Ch/PVP/Alg crosslinked with formaldehyde result 488.03% swelling ratio and 85.34% gel. Dissolution test of hydrogels in pH 1.2 releases ibuprofen less than 30%. Whereas in the pH 7.4, the release of ibuprofen by hydrogels are relatively high. Ch/PVP/Alg/Ca reach up to 34.63% in 30 minutes and 40.86% for Ch/PVP/Alg/Zn. Meanwhile Ch/PVP/Alg/CH2O can release 44.92% of ibuprofen in 30 minutes. The obtained hydrogel was characterized using infrared (FTIR) spectrophotometry, differential scanning calorimetry (DSC) and scanning electron microscopy (SEM).